The role of business agreements in defining textbook affordability and digital materials: A document analysis - John Raible; Aimee deNoyelles (Laureate Education Inc, 2015)
Adopting digital materials such as eTextbooks and e-coursepacks is a potential strategy to address textbook affordability in the United States. However, university business relationships with bookstore vendors implicitly structure which instructional resources are available and in what manner. In this study, a document analysis was conducted on the bookstore contracts for the universities included in the State University System of Florida. Namely, issues of textbook affordability, digital material terminology and seller exclusivity were investigated. It was found that textbook affordability was generally conceived in terms of print rental textbooks and buyback programs, and that eTextbooks were priced higher than print textbooks (25% to 30% markup). Implications and recommendations for change are shared. DOI: 10.18870/hlrc.v5i4.284